" دراسة تغيرات بطانة القرنية عند مرضى حسر البصر " - سليمان يوسف; جلول قحطان; محمد غيث (Latakia University Journal -Medical Sciences Series, 2019)
1.Aim: To Study changes in morphology,density,coefficient of variation in cells of corneal endothelium in patients with myopia. 2.Materials and methods: 800 patients have myopia. Corneal endothelial cells morphology (percent of hexagonality),density and coefficient of variation in cell area was evaluated using non-contact specular microscope. 3.Results: The mean endothelial cell density was 2917.98 ± 351²,the mean coefficient of variation was 30.13±5%, the mean hexagonal appearance of the cell was 60.7±19%. There were statistically significant differences in coefficient of variation ( p=0.000) and hexagonal appearance of the cell (p=0.000) but no in mean cell density (p=0.173). 4.Conclusion: More myopic eyes tend to have less cell hexagonality and high coefficient of variation. Nevertheless, there is no significant difference in mean cell density. 1.الهدف: دراسة تغيرات خلايا بطانة القرنية من حيث الشكل والكثافة ومعامل تغير الحجم عند مرضى حسر البصر 2. مواد وطرائق البحث: شارك بالدراسة 800 مريض لديهم حسر بصر . تم تقييم شكل خلايا البطانة (نسبة الخلايا السداسية) ومتوسط كثافة الخلايا ومعامل تغير حجم الخلايا بواسطة المجهر المرآوي 3. النتائج: تراوح متوسط تعداد كثافة الخلايا البطانية 351 ± 2917.98 /mm². تراوح متوسط مشعر تغير الحجوم5 ± 30.13 %. تراوح متوسط نسبة الخلايا السداسية 60.7±19%. بالتحليل الإحصائي تبين أن العلاقة بين درجة الحسر ونسبة الخلايا السداسية هامة إحصائيا P=(0.000) وكذلك بين درجة الحسر ومشعر تغير الحجوم P=(0.000) لكن لا يوجد علاقة هامة إحصائيا بين درجة الحسر وكثافة خلايا البطانة (p=0.173) 4. الخلاصة: زيادة درجة الحسر تؤدي إلى زيادة معامل تغير الحجوم وتؤدي إلى انخفاض نسبة الخلايا السداسية بينما لا يوجد أثر هام لدرجة الحسر على كثافة خلايا بطانة قرنية العين